BREAST CORE NEEDLE BIOPSY - Widyastuti, Reni; Tusta Adiputra, Putu Anda; Maliawan, Sri (E-Jurnal Medika Udayana; vol 2 no2 (2013):e-jurnal medika udayana)
Nowadays, there are many kinds of biopsy. One that can be done in breast is core needle biopsy. Core needle biopsy is a tissue sampling procedure using hollow core needle size 11-16 gauge. The operator can direct the needle directly into the palpable lesion or by using imaging. This is a safe, effective, time efficient, and less costly. The disadvantage among others, can lead to infection, scarring at the biopsy area, and spread of malignant cells in the needle route.
Keywords: Core needle biopsy